Distribution and Sources of Dissolved Black Carbon in Surface Waters of the Chukchi Sea, Bering Sea, and the North Pacific Ocean - Nakane, Motohiro; Ajioka, Taku; Yamashita, Youhei (Frontiers in Earth Science, 2017)
Pyrogenic carbon, also called black carbon (BC), is an important component in the global carbon cycle. BC produced by biomass burning or fossil fuel combustion is transported to oceans by the atmosphere or rivers. However, environmental dynamics (i.e., major sources and sinks) of BC in marine environments have not been well documented. In this study, dissolved BC (DBC) collected from surface waters of the Chukchi Sea, the Bering Sea, and the subarctic and subtropical North Pacific were analyzed using the benzene polycarboxylic acid (BPCA) method. The DBC concentration and the ratio of B5CA and B6CA to all BPCAs (an index of the DBC condensation degree) ranged from 4.8 to 15.5 µg-C L-1 and from 0.20 to 0.43, respectively, in surface waters of the Chukchi/Bering Seas and the North Pacific Ocean. The concentration and condensation degree of DBC in the Chukchi/Bering Seas were higher and more variable than those in the subarctic and subtropical North Pacific, which implies that the major factors controlling DBC distribution were different in these marine provinces. In the Chukchi/Bering Seas, the DBC concentration was negatively correlated to salinity but positively correlated to chromophoric dissolved organic matter (CDOM) quantity and total dissolved lignin phenol concentration estimated by CDOM parameters. These correlations indicated that the possible major source of DBC in the Chukchi/Bering Seas was Arctic rivers. However, in the North Pacific, where riverine inputs are negligible for most sampling sites, DBC was possibly derived from the atmosphere. Although spectral slopes of CDOM at 275-295 nm (an index of the photodegradation degree of CDOM) differed widely between the subarctic and subtropical North Pacific, the concentration and condensation degrees of DBC were similar between the subarctic and subtropical North Pacific, which suggests that photodegradation was not the only major factor controlling DBC distribution. Therefore, DBC distributions of the North Pacific Ocean were considered to be mainly controlled by atmospheric deposition of BC and subsequent losses by photodegradation and adsorption onto sinking particles. This study implies that the main influence on DBC distribution in the open ocean and the coastal ocean are atmospheric deposition and fluvial inputs, respectively.